2015
DOI: 10.4236/aim.2015.513089
|View full text |Cite
|
Sign up to set email alerts
|

A Culture-Independent and Culture-Dependent Study of the Bacterial Community from the Bedrock Soil Interface

Abstract: In nutrient limited soils, minerals constitute a major reservoir of bio-essential elements. Consequently, the release of nutritive elements during weathering is crucial. Bacteria have been shown to enhance weathering rates; however, there has been limited work that has focused on the bacterial weathering of bedrock or parent rock, which are the major sources of minerals, in nutrient limiting soils. In this study, both a culture-independent and culture-dependent approach was used to study the bacterial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Therefore, by combining culturing and non‐culture methods, the micro‐ecological effects of the addition of microbial inocula to soil can be determined with accuracy. Many studies suggested the significance of combining culture‐dependent and culture‐independent methods to gain deeper insights into population structure and diversity of complex microbial communities (Liu et al., ; Lü et al., ; Olsson‐Francis et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by combining culturing and non‐culture methods, the micro‐ecological effects of the addition of microbial inocula to soil can be determined with accuracy. Many studies suggested the significance of combining culture‐dependent and culture‐independent methods to gain deeper insights into population structure and diversity of complex microbial communities (Liu et al., ; Lü et al., ; Olsson‐Francis et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms employed by microorganisms in basaltic environments are variable and range from the production of excess protons, to the production of low molecular weight organic acids and siderophores (highly specific Fe (III) ligands), and, in some cases, and the production of extracellular polysaccharides and enzymes (Welch and Ullman, 1993 ; Vandevivere et al, 1994 ; Barker et al, 1998 ; Bennett et al, 2001 ; Wu et al, 2007 ; Olsson-Francis et al, 2015 ). These mechanisms may occur in the bulk phase or in local microenvironments, where concentrations would be much higher (Bennett et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The local vegetation at all sites was dominated by Nardus and Moliniagrasses. Samples were collected aseptically in March 2013 using corers and stored as previously described [25]. X-ray diffraction (XRD) and X-ray fluorescence (XRF) analysis confirmed the composition of the bedrock was granite.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Reads were removed from further analysis if one of the following criteria were met: 1) the read length was shorter than 150 bp, (2) number of ambiguous bases was greater than zero. The sequences were processed as previously described [25]. Rarefaction curves were generated using MG-RAST [30] and all sequences obtained in this study were submitted to MG-RAST [30] …”
Section: Bioinformatic Analysismentioning
confidence: 99%
See 1 more Smart Citation